Effect of low-intensity ultrasound-assisted washing on biochemical and gelling properties of surimi from yellowstripe scad - Sirima Sinthusamran; Jaksuma Pongsetkul; Nattaporn Rungchawala; Natthawadee Thongpiboon; Md. Anisur Rahman Mazumder; Saroat Rawdkuen; Samart Sai-Ut (My University, 2023)
Ultrasound-assisted washing had an expectant to increase the concentration of myofibrillar proteins that play an important role in gelling properties of surimi. This work investigated the effect of low-intensity ultrasound-assisted washing on surimi's biochemical and gelling properties from yellowstripe scad. Washed minced fish was obtained by conventional method or washing process through ultrasound at a frequency of 45 kHz with different steps. Physicochemical properties and protein patterns of washed minced and surimi gel were evaluated. Results showed that the washed minced fish treated by ultrasound three times (U-3) showed the highest L* (50.37±0.23) and whiteness (48.69±0.23) (p < 0.05). The ultrasound washing process significantly reduced total myoglobin content (from 2.790±0.078 to 0.178±0.029 mg/g) (p < 0.05). An increase in oxymyoglobin content was found in minced fish treated with ultrasound. Compared with the conventional method, ultrasound-assisted washing had reduced lipid oxidation as indicated by malondialdehyde content (from 2.50±0.11 to 1.81±0.11 mg/kg). The ultrasound treatment also improved water combining ability and increased the water hold capacity of the minced fish. The sarcoplasmic protein was removed, resulting in a concentration of myofibrillar protein that plays an important role in enhancing the surimi product's breaking force and gel strength. Therefore, low-intensity ultrasound-assisted washing effectively improved the gel properties of surimi from the yellowstripe scad.
Keywords: Myofibril; Sarcoplasm; Sonication; Malondialdehyde; Meat and Animal Product Quality